A Comprehensive Review of Communicative Language Teaching (CLT) in Modern Classrooms - Muhammad Yusuf Salam; Yovan Luksfinanto (Lingeduca: Journal of Language and Education Studies, 2024)
Communicative Language Teaching (CLT) has become a dominant methodology in language education, emphasizing interaction and practical communication skills over traditional grammar-focused approaches. With the increasing need for language learners to develop real-world communicative competence, CLT has been widely adopted in modern classrooms across various educational contexts. However, its implementation faces challenges such as cultural differences, teacher preparedness, and institutional constraints. This comprehensive review aims to evaluate the effectiveness and challenges of CLT in contemporary language teaching settings. This study uses a systematic review methodology, analyzing research articles, case studies, and reports published in the last two decades. The review focuses on both qualitative and quantitative studies that assess CLT’s impact on language proficiency, learner motivation, and classroom engagement. It also explores barriers to successful CLT implementation, including teacher training and resource limitations. The findings suggest that CLT has a significant positive impact on learners’ communicative competence and motivation, especially in immersive environments. However, the success of CLT varies depending on the classroom context, cultural backgrounds, and teacher expertise. Moreover, while CLT fosters a more interactive learning experience, challenges such as inadequate teacher training and a lack of suitable materials often hinder its full potential. In conclusion, CLT remains an effective approach to language teaching, but its success is contingent on overcoming implementation barriers. Further research is needed to address these challenges and to explore how CLT can be adapted to different learning environments.